PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN PADA POKOK BAHASAN PROKLAMASI KEMERDEKAAN INDONESIA - Ely Mariana (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2017)
Research and development aims to: (1) create a media development of IPS learning video to be applied as a learning media as learning source, (2) to know students’ responses about IPS learning video media in Proclamation of Indonesian Independence subject matter as learning media as learning source. The type of this research is a development research using R & D development model. This learning product development model is a systematically arranged model adapted to the characteristics of the lessons and learners. The result showed: (1) the test of IPS subject matter is very good qualification (95,00%), (2) the test of learning design is very good qualification (87,50%), (3) the test of graphic design/media is very good qualification (92,50%), (4) individual test is excellent qualification (93,33%), (5) the small group test is excellent qualification (91,39%), (6) field test is excellent qualification (97,84%). The final product of this development is in the form of a video of CD learning.